Management of anesthesia in unspecified extra-adrenal pheochromocytoma patient who used beta-blocker - Ozer, Ayse Belin; Demirel, Ismail; Duzgol, Ozgur; Ayten, Refik; Erhan, Omer Lutfi (Medknow Publications & Media Pvt Ltd, 2014)
An operation was planned for a female patient aged 59 for intra-abdominal mass. The patient was using nebivolol for hypertension. Blood pressure (BP) of the patient was raised to 200/130 mmHg during anesthesia induction. BP was gradually reduced by remifentanil infusion. Following the manipulation of the mass, BP began to increase (225/160 mmHg), thus nitroglycerin and followed nitroprusside infusion was started. Propofol (200 + 200 mg) and furosemide (20 mg) were administered intravenously. BP suddenly dropped (90/60 mmHg) following the removal of the mass, nitroglycerine, and nitroprusside infusions were stopped; remifentanil dose was decreased and fluid was quickly infused. The patient was uneventually recovered. Vanilmandelic acid level was higher in the patient and pheochromocytoma was considered.
Keywords: Adrenergic beta-antagonists; anesthesia; general; pheochromocytoma